2017
DOI: 10.5505/aot.2017.70298
|View full text |Cite
|
Sign up to set email alerts
|

Distress, Anxiety and Depression in Patients Who Have Received Hematologic Cancer Diagnosis

Abstract: ÖZET GİRİŞ ve AMAÇ:Bu çalışmanın amacı, hematolojik kanser tanısı almış ve kemoterapi tedavisi görmekte olan hastalarda distres, anksiyete ve depresyon yaşama durumlarını belirlemektir. YÖNTEM ve GEREÇLER: Tanımlayıcı kesitsel tipte yapılan çalışmanın örneklemini, hematolojik kanser tanısı almış, hematoloji servisine yatışı yapılan veya ayaktan kemoterapi tedavisi görmekte olan 75 bireyden oluşmaktadır. Hastalara kişisel bilgi formu, Distres Termometresi (DT) ve Hastane Anksiyete ve Depresyon Skalası (HADS) te… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
3
0
2

Year Published

2020
2020
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 0 publications
1
3
0
2
Order By: Relevance
“…Moreover, in the studies performed on different sample groups, it was found that the cancer patients had medium-level anxiety (25,28-30) and high-level anxiety (31)(32)(33). Furthermore, in the studies conducted on hematologic cancer patients, it was identified that the patients had medium-level anxiety (12,34).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Moreover, in the studies performed on different sample groups, it was found that the cancer patients had medium-level anxiety (25,28-30) and high-level anxiety (31)(32)(33). Furthermore, in the studies conducted on hematologic cancer patients, it was identified that the patients had medium-level anxiety (12,34).…”
Section: Discussionmentioning
confidence: 99%
“…The dependency varies as per the individuals' demographic, sociocultural, psychosocial, physical, and economic circumstances (7,10). Considering the consequences coming into play in association with cancer, it is necessary to evaluate the patient with physical, mental, emotional, sociocultural, and spiritual aspects in the healthcare approach (12,13). In this process, the objective is to enable the patient to have independence for meeting the self-care needs (8).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Tedavide gebelik nedeniyle, dikkat-yenileyici terapiler, uyku terapisi, beslenme danışmanlığı, aile terapisi gibi nonfarmokolojik yöntemler önerildi 17 . Kanser tanısı alan bireyler, kanser tanısının kanser tedavisinin zorluğuna, tedavinin yan etkilerine, hastalığın nüks etme olasılığına bağlı disstres, depresyon ve anksiyete gibi psikolojik sorunlar yaşamaktadır 18 . Gebelikte meydana gelen anatomik, fizyolojik ve hormonal değişiklikler gebede psikolojik sorunlara neden olmaktadır.…”
Section: Tartışma Ve Sonuçunclassified
“…Kanser pek çok komplikasyonu beraberinde getiren ve mortalite oranı yüksek kronik bir hastalıktır (1). Hematolojik kanserler sık görülen kanser türleri arasında yer almakta ve kan, kemik iliği veya lenfatik sistemden kaynaklı hastalıklardır (2). Dünya çapında 2020 yılında tahmini 19.3 milyon yeni kanser vakası ve yaklaşık 10 milyon kanserden ölümler gerçekleşmiştir (3).…”
Section: Introductionunclassified